A Scoping Review Green Ecopreneur dalam Pembelajaran IPA: Bentuk dan Implementasinya - Aqilatun Ni'mah (Universitas Garut, 2024)
The global environmental crisis demands a transformation in education, particularly through the enhancement of ecological awareness and the implementation of sustainability-oriented learning. This article aims to examine the forms and implementation strategies of the green ecopreneur concept in science education through a scoping review approach. This method was employed to map the scope of relevant literature and identify key patterns in the integration of green ecopreneurship within science education contexts. Literature was sourced from multiple academic databases using inclusion criteria that covered peer-reviewed publications from 2014 to 2024. Literature was sourced from multiple academic databases using inclusion criteria that covered peer-reviewed publications from 2014 to 2024. The most widely used implementation strategy is Project-Based Learning (PjBL), which effectively integrates scientific knowledge, 21st-century skills, and sustainable entrepreneurial values. However, challenges such as limited teacher understanding, lack of learning resources, and technical constraints remain significant barriers. The study concludes that green ecopreneurship holds great potential to support contextual and transformative science education, and recommends systemic support to ensure its sustainable implementation. Keywords: green ecopreneur, science education, scoping review